The development of the chondrocranium of Heleophryne purcelli Sclater with special reference to the palatoquadrate and the sound-conducting apparatus - Van der Westhuizen, C. M.(Cornelius Martin) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1959.